The tree atlas : the world's most amazing trees and where to find them - Collins, Matthew (Arboreal expert); Rutter, Thomas (Writer on gardens) (Lonely Planet Global Limited, 2024)
"Whether taking in the beautiful cherry blossoms of Japan or a beech forest's seasonal hues in France, The Tree Atlas is the ultimate guide to discovering our planet's most amazing species of tree, as well as better understanding their role in our ever changing ecosystem, and appreciating the restorative effects of visiting these natural wonders in the flesh"--